Scutellaria barbata D. Don (SBD) protects oxygen glucose deprivation/reperfusion-induced injuries of PC12 cells by up-regulating Nrf2 - Yanhua Wang; Bo Li; Xiaofen Zhang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
This study aimed to investigate the potential effect of Scutellaria barbata D. Don (SBD) on oxygen glucose deprivation/reperfusion (OGD/R)-injured PC12 cells. PC12 cells were pretreated with various concentrations of 0.1–0.8 mg/ml SBD for indicated times (12–48 h) and then subjected to OGD/R injury. Cell viability, apoptosis and proliferation were detected using MTT assay, flow cytometry, Ki67 staining and western blot. Oxidative damage was assessed by detecting MDA content, SOD activity and GSH levels. The mitochondrial membrane potential (Δψm) was measured by Rh123 staining. Western blot was performed to assess the expression levels of Nrf2 and PI3K/AKT pathway-related proteins. We found that SBD pretreatment promoted cell viability and proliferation but inhibited apoptosis of OGD/R-injured PC12 cells in dosage- and time-dependent manner. Meanwhile, SBD attenuated oxidative damage and restored mitochondria dysfunction, as evidenced by the reduced MDA content, the increased SOD and GSH levels, and the increased Δψm. Furthermore, SBD induced the expression of Nrf2 in a PI3K/AKT-dependent signalling. Knockdown of Nrf2 blocked the protective effects of SBD on PC12 cells. In conclusion, this study demonstrates that SBD pretreatment protects PC12 cells against OGD/R-induced injury. The potential mechanism may be through up-regulating the expression of Nrf2 in a PI3K/AKT-dependent pathway.